Vocal Effort and Acoustic Analysis of Gargle Phonation Versus Water Swallow in Patients With Muscle Tension Dysphonia: A Clinical Trial. - Orbelo, Diana M; Charney, Sara A; Renkert, Elisabeth; Pietrowicz, Mary; David Aka; Bayan, Semirra L; Ishikawa, Keiko (Journal of Voice, 2026)
To determine the effects of gargle phonation (GP) on self-perceived vocal improvement, vocal effort, acoustic parameters, and speech rate in patients with muscle tension dysphonia (MTD). We hypothesized that GP would improve voice, reduce phonatory effort, and alter acoustic and speech measures. Prospective randomized, single-blind cross-over clinical trial Thirty-four participants (26 females, 8 males; average age 53 years) who were diagnosed with MTD completed the Voice Handicap Index-10 (VHI-10) and were assigned three study conditions: Baseline (B), GP, and Water Swallow (WS; sham), presented in one of two counterbalanced orders B-WS-GP (WS1st) or B-GP-WS (GP1st). Participants recorded stimuli from the Consensus Auditory-Perceptual Evaluation of Voice (CAPE-V) and rated their perceived vocal effort and vocal improvement. F0, vocal intensity, cepstral peak prominence (CPP), and speaking rate were measured. Average VHI-10 scores by group were 16 (min/max 2–29) for WS1st and 15 (min/max 3–40) for GP1st. About 73.5% reported more vocal improvement after GP, 17.65% after WS, and 8.8% noted no difference between conditions. Reduced effort was reported after GP, compared to B (P < 0.001) and WS (P = 0.005). Lower effort was also reported after the WS condition, compared to B (P = 0.011). Key acoustic findings included an increase in F0 after GP for sustained /i/ for females. CPP was significantly higher for females reading CAPE-V sentences after GP, when GP preceded WS, compared to B (P = 0.004) and WS (P = 0.003). Speech rate was faster for females after GP versus B (P = 0.029). GP may be beneficial in the treatment of MTD. CPP may be a useful marker for vocal improvement after GP for women with mild MTD. Further studies would benefit from having more male participants and those with moderate and severe MTD.